Cardiopulmonary Resuscitation during Covid-19 Pandemic : A Review - Yanny Trisyani; Donny Nurhamsyah; Karti Nur Aryanti; Nabila Rifa Zahara Heriawan; Guztap Jabarul Haq; Indah Enriani Wulansari; Nilamsari Nilamsari; Burhan Nurdin; Intan Madulara (Universitas Padjadjaran, 2021)
Cardiopulmonary Resuscitation (CPR) is a procedure that can be done before the arrival of ambulance which aims to save lives of cardiac arrest patients. In covid-19 pandemic, safe CPR is still needed by considering the safety of patients and rescuers. The study aims to determine best method for performing CPR during covid-19 pandemic. The Method is literature review, with database used is Google Scholar, Pubmed and Ebscohost which obtained 10 articles. The results are to permorming CPR using personal protective equipment, minimized the provision of ventilation, use a surgical maskand use the LUCAS 3 aid for chest compressions.. The conclusion is to implement CPR in the covid-19 pandemic, must use PPE at least use surgical mask for rescuers and victim, only perform chest compressions without providing ventilation, , perform compression in prone position, and compression cycle for 2 helpers was done with alternate after 2-3 cycles.